Subarachnoid hemorrhage-associated brain injury and neurobehavioral deficits are reversed with synthetic adropin treatment through sustained Ser1179 phosphorylation of endothelial nitric oxide synthase - Dodd, William S.; Patel, Devan; Laurent, Dimitri; Lucke-Wold, Brandon; Hosaka, Koji; Johnson, Richard D.; Chalouhi, Nohra; Butler, Andrew A.; Candelario-Jalil, Eduardo; Hoh, Brian L. (Frontiers in Stroke, 2024)
Background: Subarachnoid hemorrhage (SAH) is a life-threatening vascular condition without satisfactory treatment options. The secreted peptide adropin is highly expressed in the human brain and has neuroprotective effects in brain injury models, including actions involving the cerebrovasculature.Here, we report an endothelial nitric oxide synthase (eNOS)-dependent effect of synthetic adropin treatment that reverses the deleterious effects of SAH.We tested the molecular, cellular, and physiological responses of cultured brain microvascular endothelial cells and two mouse models of SAH to treatment using synthetic adropin peptide or vehicle.Results: SAH decreases adropin expression in cultured brain microvascular endothelial cells and in murine brain tissue. In two validated mouse SAH models, synthetic adropin reduced cerebral edema, preserved tight junction protein expression, and abolished microthrombosis at 1 day post-SAH. Adropin treatment also prevented delayed cerebral vasospasm, decreased neuronal apoptosis, and reduced sensorimotor deficits at seven days post-SAH. Delaying initial treatment of adropin until 24 hours post-SAH preserved the beneficial effect of adropin in preventing vasospasm and sensorimotor deficits.Mechanistically, adropin treatment increased eNOS phosphorylation (Ser1179) at one & seven days post-SAH. Treating eNOS -/-mice with adropin failed to prevent vasospasm or behavioral deficits, indicating a requirement of eNOS signaling.Adropin is an effective treatment for SAH, reducing cerebrovascular injury in both the acute (1 day) and delayed (7 days) phases. These findings establish the potential of adropin or adropin mimetics to improve outcomes following subarachnoid hemorrhage.